The effects of service learning on students' personal, cognitive, and social learning outcomes: Towards building a theoretical model - Mamauag, Marife Molina (Animo Repository, 2018)
Theoretical debates whether service learning (SL) will indeed generate transformational change in student learning processes continue to linger over time. Unlike in the western setting where service learning first began, it has not been well-researched in Asian contexts, particularly in Malaysia. Most previous studies were using qualitative research approach, and there has been a dearth of quantitative research especially on theoretical model-building. The primary aim of this study was to determine the effects of service learning on students personal insight, cognitive and social development outcomes. Using explanatory sequential mixed methods research design, classes of students who took subjects that have a service learning component were purposely selected. Phase 1 entails a quantitative approach using survey (pretest vs. posttest) and structural equation modeling, while Phase 2 entails a qualitative research using thematic analysis of reflection papers written by the student-participants. Using an SL Behavior Scale, findings show significant changes in the personal insight, cognitive development, and social capital among 285 freshmen (aged 17 to 26) after experiencing their service learning project. The emerging themes in the reflection papers, indicating the great benefits the students gained after the SL experience further supported the quantitative data. However, the structural model hypothesizing moderating effects of SL design and mediating role of critical reflection on student learning outcomes was found to have poor fit to the sample data, contrary to findings of several previous studies. Given the limitations of this study, a new conceptual framework has been offered for other researchers to review, test and critique. Implications as to teaching, instruction and curriculum for service learning are also discussed to advance the theory and practice of service learning that better fits to the cultural milieu of Asia, particularly in Malaysia where this study was conducted.